THE DEVELOPMENT OF MATHEMATICS MODULE WITH COOPERATIVE LEARNING TYPE OF GROUP INVESTIGATION IN ALGEBRAIC FORM MATERIAL FOR SMP - Misda Wati; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Learning and teaching material is a set of information that is very much needed to implement learning. Teachers and students need additional teaching materials in modules and learning models to facilitate algebraic material delivery. This study aims to develop teaching materials in mathematical modules covering material about algebra for class VII of junior high school with learning type Group Investigation (GI). This study's subjects were students of SMP Negeri 2 Prambanan and Junior High School (SMP) Muhammadiyah Ngemplak. The technique of collecting data uses observations, interviews, and questionnaires conducted before developing the product. The research instrument used was a need response and questionnaire to assess the module being developed using a Likert scale. Based on the research assessment results from material experts, the average score was 72, which was included in very good criteria. Simultaneously, the assessment of media experts is 82, which belongs to very good criteria. Students' response to the module at the trial stage is 93.09, and the response at the stage of the trial use is 105.61; both are in the good and very good category. Based on the students' expert assessment and response, the cooperative learning module type of investigation group is suitable for the learning process.